2013
DOI: 10.1159/000354416
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma Size: Platelets, γ-Glutamyl Transpeptidase, and Alkaline Phosphatase

Abstract: Background: Thrombocytopenia is a cirrhosis surrogate which is associated with hepatocellular carcinoma (HCC) development. Aims: To compare the clinical characteristics of HCC in the presence and absence of thrombocytopenia. Methods: The baseline clinical data of a large cohort of randomly presenting, biopsy-proven HCC patients was examined for phenotypic patterns, after organizing the data by tumor size and subdivision into tumor size terciles. Results: Small tumor size tercile I patients had the lowest plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 70 publications
7
29
0
Order By: Relevance
“…Similar to the results of our previous study in 2007, macronodular cirrhosis was reported to be an independent factor for the evaluation of recurrence because of its underlying malignant transformation of liver cirrhosis . The results of this study and previous studies indicate that increased GGT is closely associated with the development of HCC because of its positive correlation with tumor size and poor OS . A prognostic nomogram for recurrence prediction in HCC patients was constructed by Ju Hyun Shim in 2015.…”
Section: Discussionsupporting
confidence: 86%
“…Similar to the results of our previous study in 2007, macronodular cirrhosis was reported to be an independent factor for the evaluation of recurrence because of its underlying malignant transformation of liver cirrhosis . The results of this study and previous studies indicate that increased GGT is closely associated with the development of HCC because of its positive correlation with tumor size and poor OS . A prognostic nomogram for recurrence prediction in HCC patients was constructed by Ju Hyun Shim in 2015.…”
Section: Discussionsupporting
confidence: 86%
“…Similar findings for HCC metastasis have been noted previously [29,30,31]. Lower levels of cirrhosis, absence of thrombocytopenia (low platelets being a reflection of liver fibrosis) and large sizes of HCCs have been documented together [32]. Since large-size HCCs can also occur in cirrhosis, the absence of cirrhosis as a permissive factor in allowing expansion of HCCs without causing patient death from parenchymal destruction can only be a partial explanation of the inverse relationship between HCC size and cirrhosis [33].…”
Section: Discussionsupporting
confidence: 84%
“…In that group, the mean MTD was 3.72 cm in the thrombocytopenia subgroup, compared to 8.78 cm in the normal platelet subgroup. The relationship between blood platelet levels and MTD is also depicted in FIGURE 2, in which an increase in tumor size was found to be associated with a significant increase in mean platelet values, as reported in other analyses [27,28]. …”
Section: Resultssupporting
confidence: 74%
“…GGTP has been found to be a useful tumor marker by others, especially in low AFP HCCs [21,29,3033] and so, to a lesser extent has ALKP [34]. Platelets were found to be associated with an increase in MTD, especially for the larger size tumors, but there was an association between MTD and platelet numbers (TABLE 4 and FIGURE 2), as noted elsewhere [27,28] and there was a greater percent of PVT in the larger tumors (TABLES 2, 4 and FIGURE 1). The reason for this is unclear.…”
Section: Discussionsupporting
confidence: 59%